2006
DOI: 10.1038/sj.eye.6702397
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of primary rhegmatogenous retinal detachment in Taiwan

Abstract: Purpose To investigate the epidemiological characteristics and related risk factors for primary rhegmatogenous retinal detachment (RRD) in Taiwan. Methods The case-control study was based on retrospective chart review of hospital patients treated for primary RRD from 1995 to 2001, inclusively. The preoperative fundus findings and refractive status were collected for each patient. Controls were selected from a nationwide survey of visual impairment in the adult population during the same period. Risk factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 28 publications
6
30
0
Order By: Relevance
“…Besides, we noted bimodal age peaks of RRD in our study, which has also been reported in previous studies on Chinese patients 12 14. As high myopia is an important risk factor for RRD in younger patients,14 the higher incidence of RRD in the young patients in this study may be due to the high prevalence of myopia in these patients in Taiwan 7…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Besides, we noted bimodal age peaks of RRD in our study, which has also been reported in previous studies on Chinese patients 12 14. As high myopia is an important risk factor for RRD in younger patients,14 the higher incidence of RRD in the young patients in this study may be due to the high prevalence of myopia in these patients in Taiwan 7…”
Section: Discussionsupporting
confidence: 88%
“…The median (50 years) and mean (47.76±0.67 years) ages in the present study are younger than reports from Western countries,9 10 13 but similar or older than reports including other Chinese populations 11 14. Differences in the mean age of patients with RRD between different ethnic groups was also reported by Chandra et al ,15 who reported that patients from South Asia had a younger age at onset and more myopic refraction than patients in Europe.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast, Chou et al [20] found males to be significantly more prone to RRD than females by an odds ratio of 2.15. Similarly, in our case series, the male-to-female ratio was 3.3.…”
Section: Discussionmentioning
confidence: 84%
“…67 This increased risk with increasing refractive error has been quoted as an odds ratio of 1.33 times per diopter of myopia in the adult Taiwanese population. 68 Retinal detachment is often a secondary complication of a macular hole. Macular holes in themselves can be devastating to visual acuity.…”
Section: Retinal Detachmentmentioning
confidence: 99%